Role of colour doppler ultrasound in the evaluation of hemodialysis arteriovenous access maturation and its correlation with success rate - Alka Agrawal; Prachi Shukla; Mayank Patidar; Suhas Kattigowda (Journal of Preventive and Complementary Medicine)
Background: Chronic kidney disease (CKD) is a significant global health issue, with many patients with end-stage renal disease (ESRD) requiring hemodialysis. Arteriovenous fistulas (AVFs) are the preferred form of vascular access; however, nearly half fail to mature adequately for dialysis.Objective: This study aims to investigate the role of Doppler ultrasound in evaluating AVF maturation and its correlation with clinical success.Methods: A one-year prospective observational study was conducted at a tertiary hospital in India, involving 68 patients referred for AVF evaluation six weeks post-creation. Colour Doppler ultrasound was used to measure blood flow, vein diameter, and depth from the skin. Data were analyzed using SPSS version 26, employing chi-square tests and independent t-tests (p<0.05).Results: The mean age of participants was 52 years, and 47% had diabetes. Doppler ultrasound indicated that 77.9% of AVFs were mature; however, only 61.7% achieved clinical success. Blood flow exceeding 600 ml/min and vein diameter greater than 6 mm were strongly correlated with successful outcomes (p<0.001). End-to-side anastomosis demonstrated better maturity rates compared to side-to-side anastomosis (p=0.01). Common complications included thrombosis (14.7%) and diffuse subcutaneous edema (17.6%).Conclusion: Doppler ultrasound is a reliable and objective tool for assessing AVF maturity and predicting functionality. It effectively identifies critical factors such as blood flow and vein size early in the process, allowing for timely interventions to enhance dialysis outcomes. Further research should focus on integrating Doppler findings with patient characteristics to optimize AVF management.